Essential Company Law in Malaysia : Navigating the Companies Act 2016 - Chan, Wai Meng, 1962-, author 292292 (Subang Jaya, Selangor : Thomson Reuters Asia Sdn Bhd, 2021)
Presenting the law in a clear and concise style, this updated second edition guides and supports a quick understanding of the Malaysian company law system. Regular reference is made to the provisions of the Companies Act 2016 to enable the reader to appreciate the statutory scheme regulating companies in Malaysia. Illustrations are used to clarify concepts and cases are cited for reference. Mind maps have been included to assist a quick appreciation of key concepts and procedure. Comparison is made with the former scheme under the Companies Act 1965 where relevant and helpful comments are included to aid the analysis of more difficult areas of the law. Each chapter begins with its learning objectives, presents the essential principles in succinct paragraphs and concludes with a summary to ensure that the reader obtains a clear understanding of the subject matter covered. A section titled “Points to Ponder” highlights difficult areas which may merit further discussion and consideration. The Appendix to the book contains a useful comparison of key provisions in the Companies Act 1965 and the Companies Act 2016. Changes made by the Companies Act 2016 Reprint and the Companies (Amendment) Act 2019 have been covered, including the requirements for the execution of documents and the conditions for loans to directors. This book is especially suitable for non-law degree students who take Company Law in their course of study as well as candidates taking MAICSA, ACCA, MICPA and MIA examinations. It can also be of interest to practitioners who need a quick refresher on basic principles and those who want to learn more about the general law relating to companies and how the Companies Act 2016 impacts their business.